Satisfação e comprometimento organizaconal em cooperativas agrícolas - Flaviano, Viviane (2014)
This study had as motivations the gaps on theories of satisfaction and organizational commitment involving organizations such as Cooperatives, specifically agricultural cooperatives. The main objective is to identify the relations between Satisfaction and Organizational Commitment. To analyze the organizational commitment, it was used the scale developed by Medeiros and Enders (1998) and the satisfaction scale was validated. For this purpose, it was made a survey research , of descriptive character and quantitative nature, with 305 members of four agricultural cooperatives in the state of Rio Grande do Sul. Regarding Satisfaction in Cooperative five factors were found, namely the Service, Input, Social and Economic, Location and Service Structure and Physical appearance. Regarding the organizational commitment in relation to members, the results indicate a high affective and instrumental commitment. By the test, it is possible to observe a relationship between the profile variables and factors of satisfaction, in which the cooperatives with more than twenty years have relation associated with the Location Service and the Cooperative. Members who do not hold a management position has major concerns with the Service, Input and social and economic aspect of their cooperative. On the subject of the cooperative of college graduates and those who participate in activities or meetings more than once or twice a year, are committed instrumentally, while those who do not occupy a management position have affective commitment. By establishing relationships between constructs may be evident that there are correlations, in its majority, moderate. Finally, regarding the relations between satisfaction and organizational commitment relationships, it was observed a strong correlation between affective commitment and Service factor, a moderate correlation in most of the factor and weak only between the Instrumental focus and the Service factor.